Workplace deviant behaviour: Study on bank employees in Klang Valley, Malaysia - Ibnu Khaldoon, Ahmad Zakuan (2015)
The purpose of this study was to determine the relationship between workload, work stress, role conflict, emotional exhaustion, and workplace deviant behaviour. Although a lot of previous studies have examined the workplace deviant behaviour, but research on the relationship between workload, work stress, role conflict, role ambiguity and workplace deviant behaviour were studied in separate studies. For this purpose a total of 140 bank officers who work in bank around Klang Valley have been selected as respondents for this study. Descriptive analysis (mean, frequency, mode and standard deviation) and the inference analyses (Pearson correlation and multiple regression analysis) were used. The findings indicate a low level of workplace deviant behaviour. The result of correlation analysis between the variables showed a significant relationship between workload, work stress, role conflict, role ambiguity and workplace deviant behaviour. The result of multiple regression analysis indicated role conflict was the largest contributor to workplace deviant behaviour. This study has practical implications in terms of where the organization should take into account the role conflict as a high potential to increase workplace deviant behaviour.